2015
DOI: 10.5152/ejp.2015.14633
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Mechanical Ventilation Knowledge Level of the Nurses: A Questionnaire Survey in a Tertiary Care Training and Research Hospital

Abstract: Objective: The correct use of necessary equipment is the key for a successful noninvasive mechanical ventilation (NIMV) practice. Trained health care personnel are important part of the practice. The current study was conducted to that end, with the aim of determining the level of knowledge about NIMV of nurses working in a training and research hospital as descriptive. Methods:The study was conducted with 147 nurses who are working at Yedikule Chest Diseases and Thoracic Surgery Training and Research Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 25 publications
(25 reference statements)
0
2
0
14
Order By: Relevance
“…This is a fact that especially for the skills which generally nurses are responsible for such as choosing the appropriate NIV mask size and fitting it correctly. This is probably due to the low level of participation in the training sessions led by training nurses and practices on low-quality simulators, insufficient observation of reallife practices (6,8). Montravers et al ( 9) surveyed 32 intensive care units all over France and found that only 39% of the nurses received NIV training and this training was provided by physicians in 87% of them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a fact that especially for the skills which generally nurses are responsible for such as choosing the appropriate NIV mask size and fitting it correctly. This is probably due to the low level of participation in the training sessions led by training nurses and practices on low-quality simulators, insufficient observation of reallife practices (6,8). Montravers et al ( 9) surveyed 32 intensive care units all over France and found that only 39% of the nurses received NIV training and this training was provided by physicians in 87% of them.…”
Section: Discussionmentioning
confidence: 99%
“…Sorensen et al (11) conducted a study in 2012 and they showed that experienced intensive care unit nurses are successful in ensuring patient adaptation to NIV, providing effective ventilation, and approaching carefully patients' perceptions of NIV. The healthcare professional who manages NIV therapy must be experienced, skilled, and high level of knowledge of the NIV therapy; this is the key component of success in practice (8). NIV training programs should include the sub-headings of the indications of NIV therapy, correct and effective mask choosing and fitting, correct use of ventilator equipment, adjusting ventilator settings, general maintenance of the ventilator, and solving problems in critical situations (12).…”
Section: Discussionmentioning
confidence: 99%
“…Elliott ve arkadaşlarının yaptığı çalışmaya göre, NIMV ile ilgili eğitim programları içeriğinde NIMV tedavisininn neden kullanıldığı, uygun maskenin uygun hastaya takılması, ventilatör ekipmanlarının tanınması ve düzgün kullanılması, ventilatör ayarlarının değişikliklerinin nasıl yapılacağı, cihazın genel bakım ve temizliği gibi konuların olması gerektiğini belirlemişlerdir (7). Tarhan ve arkadaşlarının yaptığı anket çalışmasında kadın cinsiyetin erkeklere göre NIMV bilgi düzeyi daha yüksek olarak bulunmuştur (5). Bizim çalışmamızda ise cinsiyet, yaş, mesleki deneyim ve NIMV ilgili eğitim alıp almamanın NIMV bilgi düzeyini etkilemediği belirlenmiştir.…”
Section: Discussionunclassified
“…NIMV'e bağlı yüz bölgesi basınç yaralanmalarının önlenmesi için, 24 saat hasta izlemi yapan sağlık profesyonelleri olarak hemşireler; risk altındaki hastaları tedavi öncesi tespit etmeli ve buna yönelik hemşirelik girişimlerinde bulunmalıdırlar. 5,6 Basınç yaralanmaları; basınç, sürtünme ve/veya yırtılmaya maruz kalan ve genellikle kemik çıkıntıları üzerinde ortaya çıkan deri ve deri altı doku hasarıdır. 2,7 Basıncın yoğunluğu, süresi, doku toleransı, bireysel ve çevresel faktörler basınç yarası oluşumunu etkilemektedir.…”
unclassified
“…Yüz bölgesinde basınç yaralanmalarının başlıca sebebinin; genellikle cihazların nasıl kullanılacağı, ne sıklıkla çıkarılabileceği ve derinin muayene edilmesi konusundaki bilgi eksikliğiyle ilişkili olduğu gösterilmektedir. [4][5][6]8 NIMV uygulamasının başarıya ulaşması için hemşirelerin; yüz bölgesindeki basınç yarası sorunlarını öngörmek, önlemek ve yönetmek için etkin stratejiler belirlemeli ve uygulamalıdır. Literatürde NIMV kaynaklı basınç yaralanma sıklığı ve nedenlerinin ortaya konduğu çalışmaların oldukça sınırlı olduğu görülmektedir.…”
unclassified